Quantitative risk assessment on the dietary exposure of Finnish children and adults to nitrite. Issue 1 (2nd January 2016) - Suomi, Johanna; Ranta, Jukka; Tuominen, Pirkko; Putkonen, Tiina; Bäckman, Christina; Ovaskainen, Marja-Leena; Virtanen, Suvi M.; Savela, Kirsti
ABSTRACT: Nitrite intake from the consumption of cured meat and tap water was estimated for Finnish children of 1, 3 and 6 years as well as Finnish adults of 25–74 years. Nitrite content in the foods was measured by capillary electrophoresis, and was then used together with individual food consumption data from the FINDIET 2007 and DIPP studies in a stochastic exposure assessment by a Monte Carlo Risk Assessment (MCRA) program. Nitrite intake from additive sources and tap water was assessed, and more than every 10th child between the ages 3 and 6 years was estimated to have a nitrite intake exceeding the acceptable daily intake (ADI) of nitrite. The high exposure levels were caused by frequent consumption of large portions of sausages, up to 350 g day –1 or 750 g in 3 days, among the children. Median nitrite intake from cured meat was 0.016, 0.040, 0.033 and 0.005 mg kg –1 body weight day –1 for children of 1, 3 and 6 years and adults, respectively. Bayesian estimation was employed to determine safe consumption levels of sausages and cold cuts for children, and these results gave rise to new national food consumption advice. Graphical Abstract: